TIGA STRATEGI KOMUNITAS GENKOMPAK MENINGKATKAN KETERAMPILAN PUBLIC SPEAKING GENERASI MUDA - Haris, Muhammad; Adilah, Ananda Refiona; Laksana, Bayu Indra (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
ABSTRACT The aim of this study is to provide valuable insight into the GenKompak community's strategy to improve the public speaking skills of the younger generation and its contribution to the social development and personal branding of the younger generation. To explain this, the approach used in this research uses a qualitative approach by describing all visible phenomena by collecting data through participant observation, interviews and documentation. From the studies conducted, it was found that there were three strategies carried out by the GenKompak community to improve the public speaking of the younger generation, namely through the stage program to make speaking fluently, the story sharing program, comparative studies and collaboration, the GenKompak service program. Meanwhile, its contribution is to improve the communication skills of the younger generation, increase self-confidence, develop leadership abilities, encourage the younger generation to participate in discussions and problem solving and promote public awareness about important issues.